Synthesis of Novel Biologically Active Proflavine Ureas Designed on the Basis of Predicted Entropy Changes - Janovec, Ladislav; Kovacova, Eva; Semelakova, Martina; Kvakova, Monika; Kupka, Daniel; Jager, David; Kozurkova, Maria (Molecules (Basel, Switzerland), 2021)
A novel series of proflavine ureas, derivatives 11a-11i, were synthesized on the basis of molecular modeling design studies. The structure of the novel ureas was obtained from the pharmacological model, the parameters of which were determined from studies of the structure-activity relationship of previously prepared proflavine ureas bearing n-alkyl chains. The lipophilicity (LogP) and the changes in the standard entropy (ΔS°) of the urea models, the input parameters of the pharmacological model, were determined using quantum mechanics and cheminformatics. The anticancer activity of the synthesized derivatives was evaluated against NCI-60 human cancer cell lines. The urea derivatives azepyl 11b, phenyl 11c and phenylethyl 11f displayed the highest levels of anticancer activity, although the results were only a slight improvement over the hexyl urea, derivative 11j, which was reported in a previous publication. Several of the novel urea derivatives displayed GI50 values against the HCT-116 cancer cell line, which suggest the cytostatic effect of the compounds azepyl 11b-0.44 μM, phenyl 11c-0.23 μM, phenylethyl 11f-0.35 μM and hexyl 11j-0.36 μM. In contrast, the novel urea derivatives 11b, 11c and 11f exhibited levels of cytotoxicity three orders of magnitude lower than that of hexyl urea 11j or amsacrine.
Keywords: Inhibitory Concentration 50; Models, Molecular; Humans; Entropy; entropie; Urea; inhibiční koncentrace 50; Proflavine; lidé; molekulární modely; cytostatic activity; molecular design; močovina; Kinetics; Chemical Phenomena; Male; proflavine ureas; chemické jevy; fibroblasty; proflavin; cytotoxicity; mužské pohlaví; kinetika; Fibroblasts